2010
DOI: 10.1158/1541-7786.mcr-09-0443
|View full text |Cite
|
Sign up to set email alerts
|

The MicroRNA Profile of Prostate Carcinoma Obtained by Deep Sequencing

Abstract: Prostate cancer is a leading cause of tumor mortality. To characterize the underlying molecular mechanisms, we have compared the microRNA (miRNA) profile of primary prostate cancers and noncancer prostate tissues using deep sequencing. MiRNAs are small noncoding RNAs of 21 to 25 nucleotides that regulate gene expression through the inhibition of protein synthesis. We find that 33 miRNAs were upregulated or downregulated >1.5-fold. The deregulation of selected miRNAs was confirmed by both Northern blotting and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
207
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 208 publications
(241 citation statements)
references
References 36 publications
26
207
1
4
Order By: Relevance
“…27,[37][38][39] Interestingly, our miRNA expression data were highly consistent with those of a previous study, 32 which found that miR-205, miR-222 and miR-31 were underexpressed in PCa. Genome-wide miRNA expression signatures can rapidly and precisely reveal aberrant expression of miRNA in cancers.…”
Section: Discussionsupporting
confidence: 90%
“…27,[37][38][39] Interestingly, our miRNA expression data were highly consistent with those of a previous study, 32 which found that miR-205, miR-222 and miR-31 were underexpressed in PCa. Genome-wide miRNA expression signatures can rapidly and precisely reveal aberrant expression of miRNA in cancers.…”
Section: Discussionsupporting
confidence: 90%
“…A strong downregulation of miR-205 in prostate carcinoma was also observed by Boll and colleagues (17). We again noted reduced levels of miRNAs like miR-143, miR-145, miR-320a, or miR-424 as previously described (5). In comparison with our previous profiling, some miRNAs, such as miR-223, miR-221, or miR-27a, remained unchanged in this analysis.…”
Section: Mirna Profiling Of Normal Prostate Tissues and Prostate Carcsupporting
confidence: 90%
“…The results of the deep sequencing analysis (covering only major miRNA transcripts) are shown in Supplementary Table S3. The relative expression levels of the miRNAs were comparable and also matched the results of our previous study of healthy prostate tissue (5). The profiling of the two pools of nonmalignant prostate tissue yielded comparable results for the samples from the corresponding nonmalignant part of the prostate and healthy prostate tissue obtained after radical cystectomy.…”
Section: Mirna Profiling Of Normal Prostate Tissues and Prostate Carcsupporting
confidence: 84%
See 1 more Smart Citation
“…Downregulation of let-7b, miR-1, miR-133a, miR-143, miR-145, miR-221 and miR-222 and upregulation of miR-25, miR-93, mir-96, miR-183, miR-182 or miR-301b has been reported in PCa when compared with benign prostate hyperplasia or normal prostate tissue by at least one research group (Volinia et al, 2006;Porkka et al, 2007;Ozen et al, 2008;Tong et al, 2009;Schaefer et al, 2010;Spahn et al, 2010;Szczyrba et al, 2010). In addition, overexpression of miR-96 and reduced expression of miR-221 have been associated with increased risk of biochemical recurrence and aggressive PCa (Schaefer et al, 2010;Spahn et al, 2010).…”
Section: Discussionmentioning
confidence: 99%